Health benefits, pharmacological properties, and metabolism of cannabinol: A comprehensive review - Khouchlaa, Aya; Khouri, Sara; Hajib, Ahmed; Zeouk, Ikrame; Amalich, Smail; Msairi, Soukaina; El Menyiy, Naoual; Rais, Chaimae; Lahyaoui, Manal; Khalid, Asaad; Abdalla, Ashraf N.; Ibrahim, Salma E.; et al. (Elsevier, 2024)
Cannabinol (CBN) is a non-psychoactive phytocannabinoid found in Cannabis sativa. Although overshadowed by its more well-known counterparts, such as delta-9-tetrahydrocannabinol (THC) and cannabidiol (CBD), CBN has been gaining attention due to its potential therapeutic properties. This review aims to provide insight into the molecular mechanisms underlying the pharmacological actions of CBN. CBN interacts with the endocannabinoid system (ECS), primarily targeting the CB2 and CB1 cannabinoid receptors. It acts as a partial agonist for both receptors, modulating their activity and downstream signaling pathways. Through these interactions, CBN exhibits diverse effects on various physiological processes, including pain perception, inflammation, immune response, and neuroprotection. Moreover, CBN has been shown to affect non-cannabinoid receptors, including transient receptor potential (TRP) channels, peroxisome proliferator-activated receptors (PPARs), and serotonin receptors. These interactions contribute to the modulation of pain, inflammation, and mood regulation. The molecular mechanisms of CBN also involve its antioxidant and anti-inflammatory properties. CBN has been found to reduce oxidative stress by scavenging reactive oxygen species (ROS) and inhibiting inflammatory mediators. This antioxidant activity potentially contributes to its neuroprotective effects and may have implications for the treatment of neurodegenerative disorders. Furthermore, CBN exhibits potential antimicrobial activity, acting against various bacteria, fungi, and methicillin-resistant Staphylococcus aureus (MRSA) strains. The underlying mechanisms of this antimicrobial effect are still being elucidated, but may involve disruption of microbial cell membranes and interference with microbial biofilm formation. The molecular mechanisms underlying CBN's pharmacological actions involve its interactions with the ECS, modulation of non-cannabinoid receptors, antioxidant and anti-inflammatory properties, and potential antimicrobial activity. Further research is needed to fully understand the therapeutic potential of CBN and its role in various disease states, paving the way for the development of novel therapeutic interventions. Due to its multiple interests, the isolation and synthesis of CBN has been investigated by several approaches. CBN synthesis involves various approaches, including oxidative conversions, isomerization reactions, enzymatic transformations, and biotransformation techniques. Advancements in synthetic methodologies and innovative strategies continue to contribute to the efficient production of CBN. Further research and optimization are necessary to enhance yields, purity, and scalability of the synthesis processes.